Effect of Environment Alteration in Psychological Components and Physiological Parameters during the Treadmill Running in Athletes - Marques da Rocha, Priscila Garcia (2010)
It was evaluated the effect of environmental alteration in affect, perceived exertion and in physiological parameters during treadmill running in athletes. Eighteen handball players participated in four running experimental sessions (baseline, fragmented overrated and unknown) for 20 minutes. It was analyzed: affect, rating of perceived exertion, heart rate and cortisol. Information about the running duration was manipulated. It was observed a statistically significant increase in affect during the treadmill running for the “fragmented” and “overrated ” sessions, as well as in salivary cortisol level at the 11th minute of running. The control of athletes’ affective behavior seems to relieve physiological damage when facing unknown opponents and uncertain game conditions.